Penerapan Metode Weighted Product Pada Sistem Pendukung Keputusan Pemilihan Calon Dosen Pembimbing Skripsi - Suhartini, Suhartini; Permana, Baiq Andriska Candra; Purwa, Lalu Sahibul; Putra, Hadian Mandala (Infotek: Jurnal Informatika dan Teknologi, 2024)
Decision Support System is a computer system that processes data into information to make decisions regarding specific semi-structured problems. It is specially developed to support solutions for unstructured management issues to enhance the quality of decision-making. The selection of potential thesis advisors at Hamzanwadi University's Informatics Engineering program is currently done by directly choosing an advisor while considering individual criteria or by seeking advice from peers. However, this direct selection method sometimes overlooks crucial aspects that should be prioritized. This research aims to construct a web-based Decision Support System (DSS) to assist final-semester students in the Faculty of Engineering at Hamzanwadi University in selecting their thesis advisors. The methodology employed in this Decision Support System is the Weighted Product method, which enables the calculation and comparison of multiple factors during the decision-making process. Factors analyzed in this study encompass the instructors' competency areas and the number of students they supervise. The utilization of this Decision Support System is expected to aid students in choosing an appropriate and fitting thesis advisor according to their needs. Moreover, the Decision Support System is anticipated to aid the faculty in providing information about potential thesis advisors before students finalize their choices. This research is expected to contribute to and benefit the development of information technology in the education sector